Enhanced sustainable electro-generation of a Ni (I) homogeneous electro-catalyst at a silver solid amalgam electrode for the continuous degradation of N2O, NO, DCM, and CB pollutants - Silambarasan, P.; Ramu, A. G.; Govarthanan, M.; Jung, K. D.; Moon, I. S. (ELSEVIER, 2021)
This paper reports the sustainable and enhanced generation of a Ni(I) active electro-catalyst using AgSAE as a cathode material for the sustainable degradation of N2O, NO, dichloromethane (DCM), and chlorobenzene (CB) by electroscrubbing in a series operation. The AgSAE electrode showed 1.66 times higher Ni(I) formation than the Ag metal electrode. The AgSAE achieved 20% +/- 2% Ni(I) generation in a highly concentrated alkaline medium, whereas Ag metal only achieved 12% +/- 2% Ni(I) generation at the same current density. Electrochemical impedance spectroscopy and voltammetric studies determined that the kinetics of the charge-transfer reaction was also preferential at the AgSAE, with the cathodic peak at -1.26 V vs. Ag/AgCl confirming Ni(I) formation. Initially, the change in the oxygen reduction potential and reduction efficiency of Ni(I) confirmed the removal of N2O, NO, DCM and CB. In addition, the gas Fourier transform infrared (FTIR) spectrum revealed 99.8% removal efficiency of toxic pollutants. Therefore, the regeneration of Ni(I) confirmed the sustainable removal of toxic pollutants. Furthermore, the FTIR spectra revealed the formation of NH3 during the reduction of N2O and NO. On the other hand, DCM and CB were reduced to benzene derivatives in the solution phase. In addition, a plausible reduction mechanism was derived. As a result, the AgSAE cathode exhibited two-fold higher removal efficiency of N2O, NO, DCM, and CB than the previously reported electrodes.
Keywords: MEDIATED ELECTROCHEMICAL REDUCTION; ELECTROCATALYTIC HYDRODECHLORINATION; GASEOUS TRICHLOROETHYLENE; EFFICIENT REMOVAL; MECHANISM; OXIDATION; ACIDS